Development of Coastal Radar Network at Sunda Strait - Sulistyaningsih Sulistyaningsih; Mashury Wahab; Dadin Mahmudin; Deni Permana; Yudi Yulius Maulana; Topik Teguh Estu (Universitas Ahmad Dahlan, 2016)
In this paper, development on a coastal surveillance Radar network, which is called ISRA (Indonesian Sea Radar), is presented. This Radar network was developed for surveillance at the Sunda Strait. The radar network monitors the sea traffics and activities at the Sunda Strait, which an international shipping route. There were three Radars installed for this network. All these Radars in this research use FM-CW (Frequency Modulated Continuous Wave) technology. This FM-CW has an advantage of low power consumption, low cost of operational, longer life time and high reliability. Another important feature of this Radar is the LPI (Low Probability of Intercept) capability, where the signal transmission of this Radar cannot be easily detected by a Radar detector (electronic support measure) so that this Radar can be used for a covert operation. Detected targets by Radars are shown on the display and on the web based display for the Radar network. These three Radars on the remote sites can be monitored and controlled via an internet connection from the control room in our Bandung office, which is 300 KMs away. The results of this research and development show the Indonesian capability to build a complex system such as a chain of coastal surveillance Radar network. The knowledge obtained from this research will be used to develop more advanced Radars for different applications.